Prevalence of Mental Disorders and Suicidality in Canadian Provinces. (November 2019) - Palay, Joshua; Taillieu, Tamara L.; Afifi, Tracie O.; Turner, Sarah; Bolton, James M.; Enns, Murray W.; Smith, Mark; Lesage, Alain; Bakal, Jeffrey A.; Rush, Brian; Adair, Carol E.; Vigod, Simone N.; et al.
Objective: There is limited information to guide health-care service providers and policy makers on the burden of mental disorders and addictions across the Canadian provinces. This study compares interprovincial prevalence of major depressive disorder (MDD), bipolar disorder, generalized anxiety disorder (GAD), alcohol use disorder, substance use disorders, and suicidality. Method: Data were extracted from the 2012 Canadian Community Health Survey—Mental Health ( n = 25, 113), a representative sample of Canadians over the age of 15 years across all provinces. Cross tabulations and logistic regression were used to determine the prevalence and odds of the above disorders for each province. Adjustments for provincial sociodemographic factors were performed. Results: The past-year prevalence of all measured mental disorders and suicidality, excluding GAD, demonstrated significant interprovincial differences. Manitoba exhibited the highest prevalence of any mental disorder (13.6%), reflecting high prevalence of MDD and alcohol use disorder compared to the other provinces (7.0% and 3.8%, respectively). Nova Scotia exhibited the highest prevalence of substance use disorders (2.9%). Quebec and Prince Edward Island exhibited the lowest prevalence of any mental disorder (8.5% and 7.7%, respectively). Manitoba also exhibited the highest prevalence of suicidal ideation (5.1%); however, British Columbia and Ontario exhibited the highest prevalence of suicidal planning (1.4% and 1.3%, respectively), and Ontario alone exhibited the highest prevalence of suicide attempts (0.7%). Conclusions: Significant interprovincial differences were found in the past-year prevalence of mental disorders and suicidality in Canada. More research is necessary to explore these differences and how they impact the need for mental health services.